2021
DOI: 10.1021/acs.est.1c01732
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Intracellular Complexation of Inorganic and Methylmercury in Cyanobacterium Synechocystis sp. PCC 6803

Abstract: Understanding of mercury (Hg) complexation with low molecular weight (LMW) bioligands will help elucidate its speciation. In natural waters, the rate of this complexation is governed by physicochemical, geochemical, and biochemical parameters. However, the role of bioligands involved in Hg intracellular handling by aquatic microorganisms is not well documented. Here, we combine the use of isotopically labeled Hg species (inorganic and monomethylmercury, iHg and MeHg) with gas or liquid chromatography coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…PCC6803) were obtained from the Freshwater Algae Culture Collection (FACHB) at the Institute of Hydrobiology, China. These taxa were used to represent algae and cyanobacteria frequently found in aquatic environments [32][33][34] and are widely used in biogeochemical transformation studies of Hg 59,64,66 . All freshwater algae and cyanobacteria were cultured in UTEX BG-11 medium, whereas Chaetoceros gracilis was grown in UTEX Erdschreiber medium at 23 °C under cool white fluorescent lamps for 16 h per day at a light intensity of ~50 µmol photons m -2 s -1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCC6803) were obtained from the Freshwater Algae Culture Collection (FACHB) at the Institute of Hydrobiology, China. These taxa were used to represent algae and cyanobacteria frequently found in aquatic environments [32][33][34] and are widely used in biogeochemical transformation studies of Hg 59,64,66 . All freshwater algae and cyanobacteria were cultured in UTEX BG-11 medium, whereas Chaetoceros gracilis was grown in UTEX Erdschreiber medium at 23 °C under cool white fluorescent lamps for 16 h per day at a light intensity of ~50 µmol photons m -2 s -1 .…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular thiols have also been shown to facilitate the breakdown of MeHg under 1 O2 attack 55 , as thiols can form strong complexes with MeHg and thus weaken the C-Hg bond 55,59 .…”
Section: Potential Mechanisms Of Phytoplankton Demethylationmentioning
confidence: 99%
“…The application of Hg stable isotopes in experimental studies can help elucidate Hg uptake and intracellular transformation in phytoplankton. Experimental Hg isotope enrichment studies with freshwater phytoplankton and three marine phytoplankton strains indicate that iHg and MeHg are preferentially bound to high- and low-molecular-weight dissolved organic matter (DOM), respectively, which offers clues to the disparate bioaccumulation of MeHg over iHg in phytoplankton. Several experimental studies have suggested that various phytoplankton and phototrophic bacteria strains can reduce intracellular iHg and MeHg to volatile forms of Hg, which may significantly reduce the pool of Hg available for bioaccumulation. , Seminal Hg stable isotope experiments with marine phytoplankton Isochrysis galbana confirmed that phytoplankton can effectively reduce the bioavailability of iHg and MeHg and provide new insights into the potential degradation pathways of intracellular Hg .…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%
“…The application of Hg stable isotopes in experimental studies can help elucidate Hg uptake and intracellular transformation in phytoplankton. Experimental Hg isotope enrichment studies with freshwater phytoplankton 136 and three marine phytoplankton strains 137 141 recently characterized Hg concentrations and Hg isotope ratios in marine zooplankton, which illustrated spatiotemporal differences in Δ 199 Hg. Zooplankton collected across the water column (0−1400 m) from the North Pacific Subtropical Gyre at Station ALOHA exhibited elevated Δ 199 Hg values in shallow depths and small size fractions.…”
Section: Mercury Isotope Dynamics In Biotamentioning
confidence: 99%
“…More recently, GSH was identified as the main low molecular weight binding ligand to iHg and MeHg in the cytosolic fraction of cyanobacterium Synechocystis sp. PCC 6803 (Garcia-Calleja et al 2021). PCs enzymatically produced from glutathione are additional thiols used by algae to counteract Hg negative effects (Mehra et al 1996).…”
Section: Biotic Transformation Pathways Mediated By Phytoplanktonmentioning
confidence: 99%